2020
DOI: 10.1186/s12884-020-03081-w
|View full text |Cite
|
Sign up to set email alerts
|

Serum antioxidant micronutrient levels in pre-eclamptic pregnant women in Enugu, south-East Nigeria: a comparative cross-sectional analytical study

Abstract: Background Pre-eclampsia is a common obstetric complication of pregnancy in Nigeria, and oxidative stress has been implicated in its aetiopathogenesis. Despite this fact, there is a paucity of information regarding the serum antioxidant micronutrient status of pre-eclamptic Nigerian women. The objective of the was to determine the mean serum levels of some antioxidant trace elements (copper, zinc, selenium, magnesium, manganese) in pre-eclamptic pregnant women and compare with that of healthy pregnant women in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 34 publications
1
22
1
3
Order By: Relevance
“…This finding is also in consonance with the findings of Akinloye et al [ 20 ] in Oshogbo South-West Nigeria. These lower selenium levels were also shown in many other similar studies [ 16 , 21 – 24 ]. Farzin et al [ 25 ] in Iran found a significantly lower selenium level between the preeclamptic and normotensive pregnant women, although serum selenium levels were within the normal range in both groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is also in consonance with the findings of Akinloye et al [ 20 ] in Oshogbo South-West Nigeria. These lower selenium levels were also shown in many other similar studies [ 16 , 21 – 24 ]. Farzin et al [ 25 ] in Iran found a significantly lower selenium level between the preeclamptic and normotensive pregnant women, although serum selenium levels were within the normal range in both groups.…”
Section: Discussionsupporting
confidence: 88%
“…There has been an inconsistency (decreased selenium levels and no significant difference in selenium levels in normal pregnancy and pre-eclamptic women) in the relationship between the levels of serum Selenium and the occurrence of pre-eclampsia [15][16][17]. There is a scarcity of studies concerning maternal selenium status during pregnancy in Nigeria and inconsistency in findings from published studies led to the development of this research.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, a total of 12 studies were included [5, 19-21, 23, 28-34]. Nine of them were case-control [19][20][21][29][30][31][32][33][34] and three studies [5,23,28] were cross-sectional. Studies that have been conducted in Africa and published up to August 31, 2020, were included.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Seven of the included studies showed significantly lower serum levels of Zn in preeclamptic than normotensive pregnant women [5,19,20,[29][30][31][32]. However, five studies showed non-significant association between the serum levels of Zn and pre-eclampsia [21,23,28,33,34]. Pooled meta-regression analysis showed that the serum levels of Zn is statistically decreased in preeclamptic women as compared with normotensive pregnant women with a pooled SMD of −1.45 (95% CI −2.26, −0.65) (Fig.…”
Section: Association Of Zinc With Pre-eclampsiamentioning
confidence: 99%
See 1 more Smart Citation